Stability and Taxation in Monopolistic Competition - Unveren, Burak (ECONOMICS BULLETIN, 2017)
This paper shows that the standard monopolistically competitive general equilibrium is stable if and only if a particular tax-subsidy policy induces higher utility in equilibrium. This policy is taxing profits, and subsidizing labor income at a rate less than the price markup. Therefore, the government can increase the utility in any stable equilibrium using this tax/subsidy scheme without knowing the parameters of technology and preferences. Finally, even if the laissez-faire equilibrium is unstable, a subsidy rate sufficiently close to the price markup always ensures that the equilibrium is stable. That is, the government intervention can stabilize the free market equilibrium when the equilibrium is unstable.
Keywords: CONSTRAINED SUBOPTIMALITY; INCOMPLETE MARKETS; Business & Economics